Komunikasi Organisasi dalam Mendukung Kesolidan Organisasi dan Komitmen Anggota (Studi pada PC PPM Subang) - Arie Tarjana Nataraharja; Mahdar (CV. ITTC INDONESIA, 2025)
Organizational communication plays an important role in forming solidarity and increasing member commitment. This study aims to analyze the role of internal and external communication in maintaining the stability of the organizational structure, especially in the Subang Panca Marga Youth Branch Leadership (PC PPM). With a descriptive qualitative approach, data were collected through in-depth interviews, activity observations, and organizational documentation. Effective organizational communication is the main key to maintaining solidarity and increasing member involvement in the organization, especially in PC PPM Subang. Two-way, open, and structured communication can strengthen member trust and loyalty.